Using Interferon Alfa Before Tyrosine Kinase Inhibitors May Increase Survival in Patients With Metastatic Renal Cell Carcinoma: A Turkish Oncology Group (TOG) Study - (:unkn) unknown (CIG MEDIA GROUP, LP, 2016)
Survival outcomes of interferon-alfa and tyrosine kinase inhibitors for 104 cases of metastatic renal cell carcinoma were included in this study. First-line interferon-alfa treatment before tyrosine kinase inhibitors had an additive survival affect. Background: We aimed to investigate the outcomes of interferon alfa and sequencing tyrosine kinase inhibitors (TKIs) in patients with metastatic renal cell carcinoma. Patients and Methods: This multicenter study assessing the efficacy of TKIs after interferon alfa therapy in the first-line setting in patients with metastatic renal cell carcinoma. Patients (n = 104) from 8 centers in Turkey, who had been treated with interferon alfa in the first-line setting, were included in the study. Prognostic factors were evaluated for progression-free survival (PFS). Results: The median age of the patients was 57 years. The median PFS of the patients treated with interferon alfa in the first-line was 3.6 months. A total of 61 patients received TKIs (sunitinib, n = 58; sorafenib, n = 3) after progression while on interferon alfa. The median PFS among the TKI-treated patients was 13.2 months. In the univariate analysis for interferon alfa treatment, neutrophil and hemoglobin level, platelet count, and Karnofsky performance status were the significant factors associated with PFS. In the univariate analysis for TKI treatment, neutrophil and hemoglobin levels were the significant factors for PFS. The median total PFS of the patients who had been treated with first-line interferon alfa and second-line TKIs was 24.9 months. Conclusion: This study showed that first-line interferon alfa treatment before TKIs may improve the total PFS in patients with metastatic renal cell carcinoma. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Cytokine therapy; VEGF inhibitors; Progression free survival; Sorafenib; Sunitinib; ENDOTHELIAL GROWTH-FACTOR; SUNITINIB; INTERLEUKIN-2; THERAPY; SU11248